Cellulose acetate-polyethersulfone (CA-PS) blend ultrafiltration membranes for palm oil mill effluent treatment - Idris, Ani; Ahmad, Iqbal (2007)
The objective of this research is to investigate the possibility of using ultrafiltration blended cellulose acetate (CA) and polyethersulfone (PES) membranes in the treatment of palm oil mill effluent (POME). Thus, series of distinctive formulations such as pure CA and blended CA/PES using N, N-dimethylformamide (DMF) as solvent were formulated and prepared by phase inversion method. The blended membranes were initially subjected to the separation of BSA and then POME. The performances of these membranes were evaluated in terms of pure water and permeate flux, percentage removal of total suspended solids (TSS), chemical oxygen demand (COD) and biochemical oxygen demand (BOD). Blending of 19 % CA, 1 % PES and 80 % of DMF solvent were discovered as the best membrane formulation. The morphology of the blended membranes produced were analyzed using scanning electron microscope (SEM).